Safety evaluation of an underground excavation for crusher operation - Yang, H.S.; Jang, M.H.; Kim, W.B.; Jang, Hyong Doo; Kim, J.G.; Kim, S.J. (CRC PRESS-TAYLOR & FRANCIS GROUP, 2011)
With the development of industry and increased awareness of environmental issue, eco-friendly operation of mine is gaining importance. The process of rock crushing generates noise, vibrations and enormous dust, which pollutes the surrounding environment. Mitigation of these environmental nuisances generated by the crusher is essential. In this aspect, the present study focuses on geo-mechanic based safety investigation for operating crusher in an underground mine. Geomechanical data of rocks (Q, RMR value) were investigated and fed to appropriate FLAC3D analysis for evaluating safety of the given underground excavation for installation of crusher. Safety evaluation was undertaken in 3 steps and the salient outcome is given as follows. (i) Safety evaluation of existing underground excavation without removing any pillars to provide the benchmarking results; This step revealed that the underground excavation was safe. (ii) Safety evaluation of an underground excavation assuming some part of the pillars to be removed, this step showed the generation of stress concentration in the span between the pillars and in the pillar sidewalls. (iii) Safety evaluation of an underground excavation was done assuming some pillar removed. However, after installation of suitable supports the situation was safe. © 2012 Taylor & Francis Group, London.